Analysis on Promotion and the Influence of Social Media in Restaurant Industry, Ubud, Bali, Indonesia - Ratih Tunjung Sari; Putu Eka Wirawan (Institut Pariwisata dan Bisnis Internasional, 2017)
The activities of promotion can be varied nowadays as the Internet technology has been developed to get information in real time. Digital promotion, such as from website and social media, is common to use to promote product and services, such as food and beverages in the restaurant including the services. The restaurant industry in Ubud has been growing since the start of the tourism in Ubud, Bali. Moreover, the promotion activities also need to be enhanced due to development of the technology. This research discussed further the analysis of promotion and the influence of social media to influence the decision-making process of the customers to eat food in Ubud. The aim of this research was to investigate the marketing trend in promoting restaurant in Ubud. Besides, the author aimed to find the relation between the use of social media for the restaurant to influence the decision-making process of the customers to find food in Ubud. Since Ubud is a touristic area in Bali, Indonesia, the competition of the restaurant industry should have the attention of the restaurants’ owners and managers. This research used descriptive analysis method to answer the research questions and collecting both secondary and primary data through literature review, observation, interview, and questionnaires. Based on our research, we found that digital promotion, such as social media marketing through social networks (Instagram, Facebook, Tripadvisor, and Website) could enhance the number of the customers in restaurants in Ubud.